Study on air escape in submerging process of multi-box girder attacked by flood. (1st April 2023) - Yang, Wanli; Liu, Yuxuan; Yang, Yuankang; Liu, Dewen; Ning, Jiejun; Zhang, Yuzhi; Yang, Hanbin
Abstract: During the submerging process of multi-box girder attacked by flood, the air entrapped in chambers escapes continuously, which changes the vertical component of flood force on multi-box girder remarkably. ANSYS Fluent software is employed to simulate air escape and pressure change in chambers of multi-box girder during the submerging process. Results show that when submergence ratio is small, the air in chamber is forced out from the bottom of the chamber after water rushes into the chamber, and then enters the next chamber and finally escapes from the downstream chamber; when submergence ratio is large, the air in chamber is drawn into water or vortex rushing into the chamber, and then escapes from the chamber directly. It is also found that the pressure difference in chambers is positive at the instant when the chamber is closed by flood, and gradually decreases to a negative value with the increase of submerging ratio. The decrease of the pressure difference is mainly caused by air escape and the main vortex at the bottom of girder. The fluctuation of the pressure difference is mainly caused by the periodical vortex shedding at the bottom of the girder. Highlights: The entrapped air has two different escape modes with the change of submergence ratio. The pressure difference in the chamber increases when it is closed by water, then decreases with submergence ratio. The fluctuation of pressure difference in chamber is mainly caused by the vortex shedding below girder. The averaged pressure difference varies with vortex strength and shedding intensity.